Excess Heat Factor climatology, trends, and exposure across European Functional Urban Areas - Oliveira, Ana (2022)
In Europe, regional climate change prospects indicate the urgency of adapting to extreme weather events. While increasing temperature trends have already been detected, in the last decades, the adoption of a European heatwave (HW) early-warning index is not yet consensual, partially due to the significant number of alternative algorithms, in some cases adjusted to the measurement of sector-specific impacts (as per the Expert Team on Climate Risk and Sector-specific Indices (ET-SCI)). In particular, the Excess Heat Factor (EHF) has been shown to accurately predict heat-related human health outcomes, in mid-latitude climates, provided that local summer exposure to excess heat is mostly driven by extreme air temperatures, with a lower contribution from relative humidity. Here, annual summaries of EHF-based HW detection were calculated for the European region, using daily maximum and minimum temperatures from the homogenised version of the E-OBS gridded dataset. Annual HW frequencies, duration, mean magnitude, maximum amplitude, and severity were subject to climatology and trend analysis across the European biogeographical regions, considering the 1961–1990 period as the baseline reference for anomaly detection in the more recent (1991–2018) decades. As HW-dependent morbidity/mortality affects mostly the elderly, an EHF-based HW Exposure Index was also calculated, by multiplying the recent probability of severe events per the number of people aged 65, or more, in the European Functional Urban Areas (FUAs). Results show that recent historical EHF-based patterns diverge across European Biogeographical regions, with a clear latitudinal gradient. Both the historical mean and recent trends point towards the greater exposure in the southern European Mediterranean region, driven by the significant increase of HW frequency, duration and maximum severity, especially in the last 3 decades; conversely, annual maximum EHF intensities (i.e., greatest deviations from the local 90th daily mean temperature) are mostly found in the northern and/or high altitude Boreal, Alpine and Continental regions, as a consequence of the latitudinal effect of local climatology on the HWM/HWA indices (this also translates into greater magnitudes of change, in this regions). Nonetheless, by simultaneously considering the probability of Severe HW occurrence in the last three decades, together with the log transformation of people aged 65 or more, results show that greater HW Exposure Indices affect FUAs across the whole Europe, irrespective of its regional climate, suggesting that more meaningful vulnerability assessments, early warning and adaptation measures should be prioritized accordingly.